Racial Harassment Representation in “12 Years a Slave” Film - Indira Trianti (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2024)
This study examines the representation of racial harassment in the film "12 Years a Slave." The research aims to: (1) describe the forms of racial harassment experienced in the film, and (2) analyze the reasons behind these experiences. Utilizing a descriptive qualitative method, the study draws on both primary and secondary data sources. The primary data includes the film's script and the film itself, while secondary sources comprise journal articles, books, and previous research. Data collection was conducted through note-taking, focusing on instances of racial harassment depicted in the film. The analysis employs the theoretical framework of Chen & Kleiner (1999). The findings reveal three distinct forms of racial harassment from a total of 13 instances identified: physical attacks, verbal abuse, and intimidation based on race or color. Furthermore, the research identifies that the historical context of racism in America and the legal requirement for Black individuals to possess documentation proving their freedom contribute to these experiences of racial harassment. The study concludes by discussing the implications of these findings in understanding racial harassment as portrayed in "12 Years a Slave," highlighting the significance of the Chen & Kleiner framework in analyzing such representations.